Life‐form diversity across temperate deciduous forests of Western Eurasia: A different story in the understory - Loidi, Javier; Chytrý, Milan; Jiménez‐Alfaro, Borja; Alessi, Nicola; Biurrun, Idoia; Campos, Juan Antonio; Čarni, Andraž; Fernández‐Pascual, Eduardo; Font Castell, Xavier; Gholizadeh, Hamid; Indreica, Adrian; Kavgacı, Ali; et al. (Journal of biogeography, 2021)
Aim To analyse the biogeographic patterns of Temperate Deciduous Forests (TDFs) in Western Eurasia based on different life‐forms and forests layers and explore their relationships with the current climate, Last Glacial Maximum (LGM) climate and topography. Location Western Eurasia. Taxon Vascular plants. Methods We delimited nine regions encompassing the variability of TDFs in Western Eurasia and collected 1000 vegetation plots from each. We deconstructed the plant communities into three layers, tree, shrub and floor. We used (i) generalized linear mixed models (GLMM) to analyse the influence of current climate, historical climate and topography on species richness by accounting for regional effects and (ii) redundancy analysis (RDA) with variance partitioning to describe the variation in life forms along abiotic gradients. The three forest layers were analysed jointly and separately. Results The Balkans, Alps and Carpathians appeared to be the richest in plant species, whereas the British Isles and the Hyrcanian region were the poorest. Annual temperature range and annual mean temperature were the best predictors of species richness for the whole dataset and for the shrub layer. The tree layer richness was mainly explained by the annual temperature range and by elevation, whereas the forest floor richness was more related to the annual temperature range and the annual mean temperature differences between the LGM and current climate. The current climate was the main predictor of the composition of the whole community, the tree layer and the floor layer, while the shrub layer was also influenced by historical climate. Main conclusions Our overview of the diversity of temperate deciduous forests in Western Eurasia demonstrates different patterns and drivers across life‐forms and forest layers. While the diversity of trees is mainly linked to current climatic conditions, the shrub layer is also driven by postglacial‐glacial climatic stability, suggesting a different origin from forest trees.